AB0524 Immunosuppressive Treatment in Patients with Primary SjÖgren Syndrome (PSS). (9th June 2015) - Crespo Amaya, G.; Secco, A.; Martire, V.; Marino, L.; Carlevaris, L.; Bennasar, G.; Mamani, M.; Mayer, M.; Zazzetti, F.; Velez, S.; Barreira, J.C.; Nitsche, A.; et al.
Abstract : Background: There is not enough evidence either to support the use of immunosuppressive drugs in pSS or for which specific clinical features they would be indicated. Objectives: To evaluate the most frequently immunosuppressive drugs prescribed in pSS and to describe the clinical features that determined the indication, in a multicentric cohort of Argentinean patients with pSS. To analyze the clinical characteristics of patients with immunosuppressive therapy in comparison to patients that had not received it. Methods: We analyzed subjects with pSS included in the data-base of the Argentine study group for SS (GESSAR). We considered the use of methotrexate, azathioprine, cyclophosphamide, leflunomide, mycophenolate, rituximab, belimumab and/or prednisone (>20mg/day). Results: From 431 patients, 72 (16.7%) had received immunosuppressive therapy. Female: 92%; mean age: 59 years; mean time of the disease: 5 years. Immunomodulatory treatment with hydroxychloroquine in 60%. The drugs most frequently used were:prednisone (40.3%), methotrexate (34.7%), azathioprine (23.6%), cyclophosphamide (9.7%), rituximab (5.6%), mycophenolate (4, 2%), leflunomide (2.8%), more than one drug (6.9%). The clinical features that determined the indication of therapy were arthritis (50.8%), parotid swelling (28%), purpura (19.7%), peripheral neuropathy (18.3%), pulmonary involvement (13.9%), autoimmune hepatitis (8.33%) and glomerulonephritis (5.1%). When we compared the clinical characteristics of patients with immunosuppressive treatment against patients without treatment, we found differences in age [59.4 vs 53.8; (p <0.01)], disease duration [5 vs 3; ( p <0.01)]; low C3 level [27 vs 12, 3;( p <0.01)]; arthritis [50, 8 vs 29, 4;( p <0.01)]; purpura [19.7 vs 5.5;( p <0.01)], pulmonary disease [13.9 vs 6.3;( p: 0.02)] and autoimmune hepatitis [62.5 vs 37.5;( p <0.01)]. Multivariate analysis (adjusted for age and years of disease), with immunosuppressive treatment (dependent variable), showed that arthritis (OR:2.8;95%CI:1.5-5; p <0.01), purpura (OR: 4.4; 95%CI: 1.9-10.3; p <0.01) and autoimmune hepatitis (OR: 8.7; 95%CI: 1.9-40.4; p <0.01)] were independently associated with this indication. Conclusions: A low number of our patients received treatment with immunosuppressive drugs. The most frequently prescribed drugs were methotrexate and azathioprine. The main clinical features in the immunosuppressant treated group were arthritis, purpura and autoimmune hepatitis. Disclosure of Interest: None declared